Electrical conductivity of tellurium deficient cadmium telluride - Shamsuddin M.; Nasar A.; Tare V.B. (My University, 2025)
The electrical conductivity of polycrystalline cadmium telluride having an impurity content of less than 200 ppm was measured in the temperature range of 675-975 K and in the ambient tellurium pressure varying from 1.0×10 -15 atm to 2.0×10-5 atm. The electrical conductivity of polycrystalline CdTe doped with monovalent as well as trivalent cations has also been determined under similar conditions. The conductivity was found to change from predominantly p to predominantly n type at a critical tellurium pressure depending upon the temperature. The electrical conductivity increased with the increase in ambient tellurium pressures reached a maximum, and then decreased with further increase in tellurium pressure. The results have been used to discuss the probable defect structure of CdTe particularly with reference to the variation in ambient tellurium pressure.